2021
DOI: 10.1038/s41598-021-96435-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the mTOR pathway plays a central role in dendritic cell functions after Echinococcus granulosus antigen recognition

Abstract: Immune evasion is a hallmark of persistent echinococcal infection, comprising modulation of innate immune cells and antigen-specific T cell responses. However, recognition of Echinococcus granulosus by dendritic cells (DCs) is a key determinant of the host's response to this parasite. Given that mTOR signaling pathway has been described as a regulator linking metabolism and immune function in DCs, we reported for the first time in these cells, global translation levels, antigen uptake, phenotype, cytokine tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…The weak signaling of mTOR linking to the JAK-STAT pathway implicate the expression of IL-10 is impaired. 23 The MAPK pathway also mapped to Mtor , as well as Ccr7 and Myd88 ( Fig. 4 B).…”
Section: Resultsmentioning
confidence: 93%
“…The weak signaling of mTOR linking to the JAK-STAT pathway implicate the expression of IL-10 is impaired. 23 The MAPK pathway also mapped to Mtor , as well as Ccr7 and Myd88 ( Fig. 4 B).…”
Section: Resultsmentioning
confidence: 93%
“…T cell responses in Echinococcus infection are characterized by early T helper 1 (Th1)-polarized cytokine production, which tries to eliminate the parasite at the initial stages of development and shifts to a predominant Th2 cytokine response in the later chronic stage (Vuitton, 2003). As previously described, HF induced ambiguous IL-6 and IL-10 production in BMDCs and promoted splenocytes proliferation (Rodriguez Rodrigues et al, 2021). Patients with chronic cystic echinococossis generate Th1/Th2 responses accompanied by an increased number of regulatory T cells (Baz et al, 2006).…”
Section: Introductionmentioning
confidence: 78%
“…Interestingly, it has been observed that HF stimulation plus rapamycin treatment, BMDCs showed an additive effect. This observation was clearly detected in lysosomal acidification, the induction of autophagic gene transcription and the accumulation of LC3 + compartments (Rodriguez Rodrigues et al, 2021). The reason behind this stricking effect could be that while rapamycin inhibits mTOR, HF does not; it does not even induce it, but can directly enhance autophagy pathway via activation of the Beclin-1 complex.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[23][24][25] Besides, IL-6 and TNF are related to the immune evasion of echinococcus infection. 26 Moreover, F3 is closely related to inflammatory bowel disease. 27 These conclusions indicate that our prediction results have a certain significance.…”
Section: Discussionmentioning
confidence: 99%